Biomarkers on the Day of ACL Reconstruction and Sex Predictive of Knee-related Quality of Life at 2-year Follow-up. Issue 3 (31st March 2017) - Lattermann, Christian; Jacobs, Cale A.; Whale, Caitlin; Jochimsen, Kate; Johnson, Darren L.; Reinke, Emily; Huston, Laura J.; Kraus, Virginia B.; Spindler, Kurt P.
Objectives: Regardless of surgical or conservative management, the majority of patients develop posttraumatic osteoarthritis (PTOA) within 15 years of anterior cruciate ligament (ACL) injury. In addition to MRI or radiographic evidence of cartilage degeneration, the onset of PTOA is associated with increased concentrations of chondrodegenerative and inflammatory biomarkers and reduced Knee Injury and Osteoarthritis Score Quality of Life (KOOS-QOL) scores. Postoperatively, biochemical biomarkers may offer the ability to detect the onset of PTOA earlier than traditional imaging methods; however, little is known about the ability of preoperatively collected biomarkers to predict postoperative symptoms often associated with early onset of PTOA. The purpose of this prospective study was to determine if patient demographics and biomarkers collected on the day of ACL reconstruction could accurately explain the variability in postoperative KOOS-QOL scores. We hypothesized that no combination of biomarkers collected on the day of ACL reconstruction would be associated with 2-year patient-reported outcomes. Methods: Participants included 18 patients (9 females, 9 males; age = 20.1 ± 5.2 years; height = 177.7 ± 11.9 cm; weight = 77.8 ± 18.0 kg) that had previously enrolled in a prospective randomized trial evaluating early anti-inflammatory treatment after ACL injury. As part of the initial trial, synovial, serum, and urinary biomarkers of chondrodegeneration and inflammation were collected on the day of ACL reconstruction. Patients were then contacted to complete patient-reported outcomes 2 years following surgery. A linear regression was performed to determine if a model generated from patient demographics and biomarkers on the day of surgery and could accurately explain the variability in KOOS-QOL scores at 2 years. Results: KOOS-QOL scores significantly improved from 39.9 ± 14.2 on the day of ACL reconstruction to 66.7 ± 19.7 at 2 years (p < 0.001). A model containing urinary CTX-II and sex explained 52% of the variability in 2-year KOOS-QOL scores (adjusted R 2 = 0.52, p = 0.002), with higher urinary CTX-II values and female sex associated with poorer KOOS-QOL scores. Urinary CTX-II, which is a biomarker of type II collagen breakdown, individually explained 32% of the variability in 2-year KOOS-QOL scores (p = 0.01) with sex explaining 20% of the variability (p = 0.02). Conclusion: Previous studies have demonstrated that ACL injury triggers a biochemical cascade that worsens over the first 4-6 weeks after injury. The current results demonstrated that higher levels of collagen breakdown as measured via CTX-II levels at the time of surgery was associated with worse KOOS-QOL outcomes at 2 years. This data strongly suggests that initial biochemical changes after injury may have powerful consequences for the injured knee that are not mitigated by surgical stabilization alone. Early anti-catabolic intervention after ACL injury may need to be investigated as an adjunct treatment strategy, particularly in female patients with high CTX-II levels.